A Pyrrole‐Fused Asymmetrical Electron Acceptor for Polymer Solar Cells with Approaching 16% Efficiency. Issue 1 (9th October 2020) - Luo, Zhenghui; Ma, Ruijie; Xiao, Yiqun; Ni, Fan; Liu, Tao; Zhan, Qun; Sun, Huiliang; Chen, Yuzhong; Zou, Yang; Lu, Xinhui; Yan, He; Yang, Chuluo
Abstract : Selecting suitable aromatic rings to develop asymmetric small‐molecule acceptors (SMAs) is of great significance. Herein, two asymmetric SMAs, namely, BTN‐4F and BTSe‐4F, are successfully synthesized by incorporating pyrrole and selenophene unit into the cores, respectively. Compared with the selenophene‐fused counterpart BTSe‐4F, BTN‐4F displays slightly upshifted energy levels and red‐shifted absorption spectrum (about 40 nm in film) due to the strong electron‐donating ability of N atoms in pyrrole. When matching with PM6, the BTN‐4F‐based device gives a higher power conversion efficiency (PCE) (15.82%) due to the simultaneously enhanced open circuit voltage ( V OC ), short‐circuit current density ( J SC ), and fill factor (FF), compared with those of the BTSe‐4F‐based device. The higher V OC coincides with the shallower lowest unoccupied molecular orbital (LUMO) energy level of BTN‐4F; the enhanced J SC mainly results from the broadened and enhanced absorption; the increased FF can be ascribed to the weaker bimolecular recombination, more balance charge transport, and more favorable morphology. It should be mentioned that the BTN‐4F‐based device yields a lower energy loss than that of the BTSe‐4F‐based device. Overall, the work demonstrates that pyrrole‐fused SMAs shows great potential in realizing low E loss while yielding high J SC and PCE, which paves a new way to develop high‐performance SMAs. Abstract : Two new asymmetric small‐molecule acceptors (SMAs), namely, BTN‐4F and BTSe‐4F, are designed by introducing pyrrole and selenophene into the central core, and the BTN‐4F‐based device yields a better power conversion efficiency (PCE) and lower energy loss compared with those of the BTSe‐4F‐based device.